Mass Messaging and Health Risk Reduction : Evidence from COVID-19 Text Messages in Tajikistan - Seitz, William (World Bank, Washington, DC, 2021)
Can mass public health messages change behavior during a crisis? This paper assesses the impact of a COVID-19 focused text-messaging campaign launched in May 2020 with the Ministry of Health and Social Protection of Tajikistan to encourage compliance with risk reduction measures. The initiative sent a series of informational messages to about 5.5 million mobile phone subscribers and reached at least one member of more than 90 percent of the country’s households. An individual fixed effects estimator is used to measure changes in reported behavior after a respondent lists text messages as a primary source of information about COVID-19, or alternatively when reporting an official text message in the past week. Listing text messaging as a primary source of information increased the number of reported behaviors by 0.15 units (p = 0.000) and receiving an official text message in the past week increased the number by 0.47 units (p = 0.000). These effects were driven by more positive responses for wearing masks, reducing visits with friends and relatives, reducing travel, practicing safer greetings (such as fewer handshakes), and safety-related changes at work. The results suggest that text messaging–based public health messaging was a cost-effective means of increasing awareness in a large and geographically dispersed audience during the COVID-19 pandemic and that the program led to an increase in self-reported risk reducing behaviors.